(untitled) (Journal of Fiber Bioengineering and Informatics, 2024)
Based on the image and textual data, the characteristics of the style, structure and pattern of the costumes in the Tang tomb murals were analysed using garment engineering. The size of each part of the costumes was inferred using the proportion method, and a set of formulas was summarised. Based on comparing three kinds of pattern extraction algorithms, the Canny operator combined with the morphology algorithm was optimal for pattern extraction for costume restoration. 3D virtual technology was used to digitally restore the costumes of the tomb murals of YanFei. The effect of costume restoration was evaluated according to the rank sum operation method and questionnaire results.